Injectable Self‐Healing Antibacterial Bioactive Polypeptide‐Based Hybrid Nanosystems for Efficiently Treating Multidrug Resistant Infection, Skin‐Tumor Therapy, and Enhancing Wound Healing. (28th March 2019) - Zhou, Li; Xi, Yuewei; Xue, Yumeng; Wang, Min; Liu, Yanle; Guo, Yi; Lei, Bo
Abstract: The surgical procedure in skin‐tumor therapy usually results in cutaneous defects, and multidrug‐resistant bacterial infection could cause chronic wounds. Here, for the first time, an injectable self‐healing antibacterial bioactive polypeptide‐based hybrid nanosystem is developed for treating multidrug resistant infection, skin‐tumor therapy, and wound healing. The multifunctional hydrogel is successfully prepared through incorporating monodispersed polydopamine functionalized bioactive glass nanoparticles (BGN@PDA) into an antibacterial F127‐ε‐Poly‐L‐lysine hydrogel. The nanocomposites hydrogel displays excellent self‐healing and injectable ability, as well as robust antibacterial activity, especially against multidrug‐resistant bacteria in vitro and in vivo. The nanocomposites hydrogel also demonstrates outstanding photothermal performance with (near‐infrared laser irradiation) NIR irradiation, which could effectively kill the tumor cell (>90%) and inhibit tumor growth (inhibition rate up to 94%) in a subcutaneous skin‐tumor model. In addition, the nanocomposites hydrogel effectively accelerates wound healing in vivo. These results suggest that the BGN‐based nanocomposite hydrogel is a promising candidate for skin‐tumor therapy, wound healing, and anti‐infection. This work may offer a facile strategy to prepare multifunctional bioactive hydrogels for simultaneous tumor therapy, tissue regeneration, and anti‐infection. Abstract : This paper reports an intrinsically multifunctional bioactive hybrid hydrogel for treating multidrug resistant infection, skin‐tumor therapy, and wound healing. The hybrid hydrogels display excellent self‐healing and injectable ability, as well as robust antibacterial activity, especially against multidrug‐resistant bacteria in vitro and in vivo, and also efficiently inhibits tumor growth and enhances wound healing.